2017
DOI: 10.3892/ol.2017.6176
|View full text |Cite
|
Sign up to set email alerts
|

Apogossypolone induces apoptosis and autophagy in nasopharyngeal carcinoma cells in an in vitro and in vivo study

Abstract: Nasopharyngeal carcinoma (NPC) has a high incidence and mortality rate, particularly in Southern China. Apogossypolone (ApoG2) is a novel derivative of gossypol with antitumor activity and less toxicity. The human NPC CNE-2 cell line was studied in the in vitro model; whilst 4 week-old male nude mice (BALB/c-nu) were inoculated subcutaneously with CNE-2 cells, and xenograft tumors were studied in the in vivo model. Graded concentrations of ApoG2 were used in treatment studies. In ApoG2-treated and control in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Similar to our data, ApoG2 could effectively inhibit proliferation of NPC cells that expressed antiapoptotic Bcl-2 family proteins at a high level(19). The report by Zheng et al(38) further supported the suppressive role of ApoG2 on the growth of human NPC cells by inducing apoptosis and autophagy. ApoG2 could induce apoptosis through up-regulation of Bax and down-regulation of Bcl-2, increasing reactive oxygen species (ROS) levels, inducing cytochrome C release and cleaving caspase proteins(39).…”
supporting
confidence: 91%
“…Similar to our data, ApoG2 could effectively inhibit proliferation of NPC cells that expressed antiapoptotic Bcl-2 family proteins at a high level(19). The report by Zheng et al(38) further supported the suppressive role of ApoG2 on the growth of human NPC cells by inducing apoptosis and autophagy. ApoG2 could induce apoptosis through up-regulation of Bax and down-regulation of Bcl-2, increasing reactive oxygen species (ROS) levels, inducing cytochrome C release and cleaving caspase proteins(39).…”
supporting
confidence: 91%
“…Zheng et al . reported that the regulation of gossypol derivative ApoG2 can reduce the expression of Bcl‐2, and promote apoptosis and autophagy in nasopharyngeal carcinoma CNE2 cells, thus inhibiting tumor growth . Song et al .…”
Section: Discussionmentioning
confidence: 99%
“…Bcl-2, and promote apoptosis and autophagy in nasopharyngeal carcinoma CNE2 cells, thus inhibiting tumor growth. 18 Song et al observed that autophagy is responsible for paclitaxel resistance seen in nasopharyngeal carcinoma cells. 19 Makowska et al 20 found that the autophagy levels of NPC cell CNE-2R are negatively correlated with apoptosis and radiation resistance.…”
Section: Expression Of Related Proteins In Nude Mice Xenograftsmentioning
confidence: 99%
“…Nonetheless, despite it is considered to be a favorable drug in the therapy of cancer and reaching clinical human trials, downside with gossypol was found, because of its structure which contain two aldehydic groups that linked with toxicity and as potential targets for another proteins (Baggstrom et al, 2011). Therefore, derivatives of gossypol arisen such as apo gossypol, produced by eliminating the two aldehydic groups ,for which better activity in leukemias, liver cancer ,nasopharyngeal carcinoma cells, breast cancer, prostate cancer and pancreatic cancer has been stated; furthermost significantly, it has lesser toxicity than that of gossypol (Zheng et al, 2017).…”
Section: Phenylalaninementioning
confidence: 99%